Adhesive sheet

By using an isocyrene polymer and other additives in the bonding combination layer of the adhesive tape, the problem of insufficient adhesion and deformation response in existing technologies in existing technologies is solved, and high adhesion and high adhesion and Excellent variant recovery bonding tablets are suitable for flexible electronic devices.

CN114450370BActive Publication Date: 2025-01-28AJINOMOTO CO INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080067917.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2020-09-30
Publication Date
2025-01-28
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

The prior art is difficult to provide adhesive sheets suitable for flexible electronic devices that have both high adhesiveness and deformation responsiveness and restorability.

Method used

By the bonding composition layer of the bonding composition layer composed of an isoprene polymer, plasticizer, liquid polyolefin, and/or liquid rubber by using the cross -linked structure in the adhesive tablet containing the supporting body and the bonding combination layer to form a adhesion to form a adhesion Plot.

Benefits of technology

It realizes high adhesion, deformation response and recoverable bonding tablets, and is suitable for flexible electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003567854340000191
    Figure BDA0003567854340000191
Patent Text Reader

Abstract

The present invention provides an adhesive sheet suitable for use in a member of a flexible electronic device, which has high adhesiveness and excellent responsiveness and recovery to deformation. An adhesive sheet comprises a support and an adhesive composition layer formed on the support, wherein the adhesive composition constituting the adhesive composition layer comprises: (A) an isobutylene polymer having a cross-linked structure, (B) a plasticizer, and (C) a liquid polyolefin and / or a liquid rubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet, and more particularly to an adhesive sheet suitable for use as a sealing sheet, an adhesive sheet, an optically transparent adhesive sheet (OCA), etc. in a flexible electronic device. Background Art

[0002] For a long time, electronic devices such as flat panel displays (liquid crystal displays, organic EL displays, electronic paper, etc.) and solar cells mainly use glass substrates, but glass substrates are heavy and easy to damage. If they are lightened and thinned, their strength will decrease. Therefore, in recent years, a large number of developments have been carried out on flexible electronic devices (hereinafter referred to as "flexible devices") that replace glass substrates with soft and bendable flexible substrates. In flexible devices, the breakage or peeling of components due to the stress generated when bending has become a problem. In addition, shape recovery is also required for deformation caused by bending. Therefore, for adhesive sheet materials such as sealing sheets, adhesive sheets, OCAs, etc. used in flexible devices, in addition to adhesion, high responsiveness to deformation caused by bending and excellent deformation recovery are also required (Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent document 1: Japanese Patent Application Publication No. 2018-526469. Summary of the invention

[0006] Technical problem to be solved by the invention

[0007] On the other hand, it is known that isobutylene polymers generally have excellent adhesiveness, and therefore adhesive compositions containing isobutylene polymers can be used as materials for adhesive sheets. However, when used in flexible electronic devices, they are not sufficiently satisfactory, and it is desired to develop an adhesive sheet suitable for flexible devices that has both adhesiveness and responsiveness and recovery to deformation.

[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an adhesive sheet which has high adhesiveness and is excellent in responsiveness and recovery to deformation and is suitable for use as a member of a flexible electronic device.

[0009] Technical solutions adopted to solve technical problems

[0010] The inventors of the present invention have conducted intensive research to solve the above-mentioned problems, and as a result, have found that the above-mentioned problems can be solved by providing an adhesive sheet comprising a support and an adhesive composition layer, wherein the adhesive composition layer is composed of an adhesive composition (the adhesive composition contains: an isobutylene polymer having a cross-linked structure, a plasticizer, a liquid polyolefin and / or a liquid rubber), thereby completing the present invention. That is, the present invention includes inventions having the following characteristics:

[0011] [1] An adhesive sheet comprising a support and an adhesive composition layer formed on the support, wherein the adhesive composition constituting the adhesive composition layer contains:

[0012] (A) an isobutylene polymer having a cross-linked structure,

[0013] (B) plasticizers, and

[0014] (C) liquid polyolefins and / or liquid rubbers;

[0015] [2] The adhesive sheet according to [1], wherein the plasticizer is a plasticizer that is liquid at 25°C and has a viscosity of less than 10000 mPa·s at 25°C;

[0016] [3] The adhesive sheet according to [1] or [2], wherein the liquid polyolefin and / or liquid rubber is a liquid polyolefin and / or liquid rubber that is liquid at 25°C and has a viscosity of 10000 mPa·s or more at 25°C;

[0017] [4] The adhesive sheet according to any one of [1] to [3], wherein the isobutylene polymer having a crosslinked structure comprises crosslinked bonds formed by reaction of an epoxy group with a carboxylic acid group and / or a carboxylic anhydride group;

[0018] [5] The adhesive sheet according to any one of [1] to [4], wherein the isobutylene polymer is a copolymer of isobutylene and isoprene;

[0019] [6] The adhesive sheet according to any one of [1] to [5], wherein the isobutylene polymer having a cross-linked structure is a reaction product of an isobutylene polymer having an epoxy group and an isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group;

[0020] [7] The adhesive sheet according to any one of [1] to [6], wherein the adhesive composition contains 40 to 80% by mass of an isobutylene polymer having a cross-linked structure relative to 100% by mass of the non-volatile component of the adhesive composition;

[0021] [8] The adhesive sheet according to any one of [1] to [7], wherein the adhesive composition contains 10 to 45% by mass of a plasticizer relative to 100% by mass of a non-volatile component of the adhesive composition;

[0022] [9] The adhesive sheet according to any one of [1] to [7], wherein the adhesive composition contains 10 to 45% by mass of a liquid polyolefin and / or a liquid rubber relative to 100% by mass of a non-volatile component of the adhesive composition;

[0023]

[10] The adhesive sheet according to any one of [1] to [9], wherein the adhesive sheet is used for a flexible electronic device;

[0024]

[11] The adhesive sheet according to

[10] , wherein the flexible electronic device is a flexible organic EL device or a flexible solar cell device;

[0025]

[12] An adhesive composition comprising:

[0026] (A) an isobutylene polymer having a cross-linked structure,

[0027] (B) plasticizers, and

[0028] (C) liquid polyolefins and / or liquid rubbers;

[0029]

[13] An adhesive composition comprising:

[0030] (A') an isobutylene polymer having a functional group capable of forming a crosslinked structure,

[0031] (A") an isobutylene polymer and / or a crosslinking agent having a functional group capable of reacting with the functional group of the isobutylene polymer having a functional group capable of forming a crosslinking structure to form a crosslinking structure,

[0032] (B) plasticizers, and

[0033] (C) liquid polyolefins and / or liquid rubbers;

[0034]

[14] An adhesive composition comprising:

[0035] (A-1) an isobutylene polymer having an epoxy group,

[0036] (A-2) an isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group,

[0037] (B) plasticizers, and

[0038] (C) liquid polyolefins and / or liquid rubbers;

[0039]

[15] A method for manufacturing an adhesive sheet, comprising the following steps:

[0040] The adhesive composition described in

[13] or

[14] in a varnish form is applied onto a support and heated and dried to form an adhesive composition layer having a cross-linked structure;

[0041]

[16] A method for manufacturing an adhesive sheet, comprising the following steps:

[0042] The adhesive composition described in

[14] in a varnish form is applied to a support and heated and dried to form an adhesive composition layer, in which a cross-linked structure is formed by the reaction of the epoxy group of the isobutylene polymer (A-1) having an epoxy group with the carboxylic acid group and / or carboxylic acid anhydride group of the isobutylene polymer (A-2) having a carboxylic acid group and / or a carboxylic acid anhydride group.

[0043] Effects of the Invention

[0044] According to the present invention, it is possible to provide an adhesive sheet which is excellent in adhesiveness and also excellent in responsiveness and recovery to deformation and is suitable for use in flexible electronic devices. DETAILED DESCRIPTION

[0045] The present invention is described below in conjunction with its preferred embodiments. The adhesive sheet of the present invention comprises a support and an adhesive composition layer formed on the support. The adhesive composition constituting the adhesive composition layer comprises:

[0046] (A) an isobutylene polymer having a cross-linked structure,

[0047] (B) plasticizers, and

[0048] (C) Liquid polyolefin and / or liquid rubber.

[0049] <(A) Isobutylene polymer having a cross-linked structure>

[0050] The cross-linked structure of the isobutylene polymer having a cross-linked structure (hereinafter also referred to as component (A)) used in the present invention is not particularly limited, and examples thereof include: a cross-linked structure formed by an epoxy group and a carboxylic acid group and / or a carboxylic anhydride group, a cross-linked structure formed by an epoxy group and an amino group, a cross-linked structure formed by a hydroxyl group and an isocyanate group, a cross-linked structure formed by an alkoxysilyl group, a cross-linked structure formed by an acryl group, etc. Among them, from the viewpoint of improved adhesion, improved optical properties, and reduced moisture permeability, a cross-linked structure formed by an epoxy group and a carboxylic acid group and / or a carboxylic anhydride group is preferred. That is, the isobutylene polymer having a cross-linked structure used in the present invention preferably contains a cross-linked bond formed by the reaction of an "epoxy group" and a "carboxylic acid group and / or a carboxylic anhydride group".

[0051] As the isobutylene polymer with a cross-linked structure that can be used in the present invention, there is no particular limitation as long as it is a polymer with a cross-linked structure and an isobutylene skeleton. The isobutylene polymer can be polyisobutylene as a homopolymer of isobutylene, or it can be a copolymer such as a random copolymer and a block copolymer. As copolymers, there can be mentioned: copolymers of isobutylene-isoprene, copolymers of isobutylene-n-butene, copolymers of isobutylene-butadiene, etc. From the viewpoint of adhesion and temperature stability of elastic modulus, the isobutylene polymer is preferably polyisobutylene and isobutylene-isoprene copolymer, and isobutylene-isoprene copolymer is particularly preferred. The isobutylene polymer with a cross-linked structure in the present invention can be used alone or in combination of two or more.

[0052] The number average molecular weight of the isobutylene polymer having a cross-linked structure is not particularly limited. From the viewpoint of providing good coating properties of the varnish of the adhesive composition and good compatibility with other components in the adhesive composition, it is preferably 1,000,000 or less, more preferably 750,000 or less, further preferably 500,000 or less, further preferably 400,000 or less, further more preferably 300,000 or less, particularly preferably 200,000 or less, and most preferably 150,000 or less. On the other hand, from the viewpoint of preventing depressions during coating of the varnish of the adhesive composition, allowing the formed adhesive composition layer to exhibit moisture permeation resistance, and improving mechanical strength, the number average molecular weight is preferably 1,000 or more, more preferably 3,000 or more, further more preferably 5,000 or more, further more preferably 10,000 or more, further more preferably 30,000 or more, and particularly preferably 50,000 or more. It should be noted that the number average molecular weight in the present invention is measured by gel permeation chromatography (GPC) method (polystyrene conversion). The number average molecular weight measured by the GPC method can be specifically measured using LC-9A / RID-6A manufactured by Shimadzu Corporation as a measuring apparatus, using Shodex K-800P / K-804L / K-804L manufactured by Showa Denko K.K. as a column, using toluene or the like as a mobile phase, and measuring at a column temperature of 40°C, and calculated using a calibration curve of standard polystyrene.

[0053] The content of (A) component in the adhesive composition of the present invention is not particularly limited. However, there is a tendency that the adhesion decreases if (A) component is more, from the viewpoint of maintaining sufficient adhesion, relative to the non-volatile component 100 mass % of the adhesive composition, the content is preferably below 80 mass %, more preferably below 75 mass %, more preferably below 70 mass %, further preferably below 65 mass %, particularly preferably below 60 mass %. On the other hand, from the viewpoint of improving the crosslinking density and improving the deformation recovery, relative to the non-volatile component 100 mass % in the adhesive composition, the content is preferably more than 15 mass %, more preferably more than 20 mass %, more preferably more than 25 mass %, further more preferably more than 30 mass %, further more preferably more than 35 mass %, particularly preferably more than 40 mass %.

[0054] In one embodiment of the present invention, the content of the component (A) in the adhesive composition of the present invention is preferably 15 to 80% by mass, more preferably 25 to 70% by mass, and further preferably 35 to 60% by mass, relative to 100% by mass of the non-volatile components of the adhesive composition. In another embodiment of the present invention, the content of the component (A) in the adhesive composition of the present invention is preferably 40 to 80% by mass, relative to 100% by mass of the non-volatile components of the adhesive composition.

[0055] The isobutylene polymer having a cross-linked structure can be produced, for example, by the following method:

[0056] (1) reacting an isobutylene polymer (one or more) having a functional group capable of forming a crosslinked structure with an isobutylene polymer (one or more) having a functional group capable of reacting with the functional group to form a crosslinked structure;

[0057] (2) An isobutylene polymer (one or more kinds) having a functional group capable of forming a crosslinked structure is reacted with a crosslinking agent (one or more kinds) to crosslink the polymer.

[0058] As the functional group that can form a cross-linked structure, for example, an epoxy group, a carboxylic acid group, a carboxylic acid anhydride group, an amino group, a hydroxyl group, an isocyanate group, an alkoxysilyl group, an acryloyl group, etc. can be cited. As the functional group that can react with the functional group to form a cross-linked structure, for example, when the functional group that can form a cross-linked structure is an epoxy group, it is a carboxylic acid group or a carboxylic acid anhydride group, and when the functional group that can form a cross-linked structure is a carboxylic acid group or a carboxylic acid anhydride group, it is an epoxy group. As a cross-linking agent, as long as it can react with the functional group that can form a cross-linked structure to form a cross-linked structure, there is no particular limitation, and for example, a multifunctional epoxy compound can be cited.

[0059] In the method (1), examples of the combination of a "functional group capable of forming a cross-linked structure" and a "functional group capable of reacting with the functional group to form a cross-linked structure" include a combination of an epoxy group and a "carboxylic acid group or a carboxylic anhydride group", a combination of an epoxy group and an amino group, a combination of a hydroxyl group and an isocyanate group, alkoxysilyl groups, acryloyl groups, methacryloyl groups, etc. From the viewpoint of improved adhesion, improved optical properties, and reduced moisture permeability, a combination of an epoxy group and a "carboxylic acid group or a carboxylic anhydride group" is preferred.

[0060] In the method (1), the isobutylene polymer having a functional group capable of forming a crosslinked structure and the isobutylene polymer having a functional group capable of reacting with the functional group to form a crosslinked structure may be the same. That is, the isobutylene polymer having "a functional group capable of forming a crosslinked structure" and "a functional group capable of reacting with the functional group to form a crosslinked structure" may be reacted with each other.

[0061] In the method (2), from the viewpoint of improvement in deformation recovery and optical properties, the functional group capable of forming a crosslinked structure is preferably a carboxylic anhydride group, and the crosslinking agent is preferably a polyfunctional epoxy compound.

[0062] In a preferred embodiment of the present invention, the isobutylene polymer having a crosslinked structure is a reaction product of an "isobutylene polymer having an epoxy group" and an "isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group".

[0063] The amount ratio of the isobutylene polymer having an epoxy group and the isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group in the reaction is not particularly limited as long as a suitable cross-linking structure can be formed. The molar ratio of "epoxy group" to "carboxylic acid group and / or carboxylic anhydride group" (epoxy group:carboxylic acid group and / or carboxylic anhydride group) is preferably 100:10 to 100:200, more preferably 100:50 to 100:150, and particularly preferably 100:90 to 100:110.

[0064] <(A-1) Isobutylene polymer having epoxy group>

[0065] The isobutylene polymer having an epoxy group used in the present invention (hereinafter also referred to as component (A-1)) is, for example, an unsaturated compound having an epoxy group such as glycidyl (meth)acrylate, 4-hydroxybutyl acrylate glycidyl ether, and allyl glycidyl ether, which can be obtained by graft-modifying an isobutylene polymer under free radical reaction conditions. In addition, the unsaturated compound having an epoxy group can also be free radical copolymerized with an olefin or the like.

[0066] The concentration of epoxy groups in the isobutylene polymer having epoxy groups is preferably from 0.05 to 10 mmol / g, more preferably from 0.1 to 5 mmol / g. The epoxy group concentration can be determined from the epoxy equivalent obtained in accordance with JIS K 7236-1995.

[0067] The number average molecular weight of the isobutylene polymer having an epoxy group is preferably from 20,000 to 160,000, more preferably from 30,000 to 140,000, particularly preferably from 40,000 to 120,000, from the viewpoint of bending resistance and the like.

[0068] <(A-2) Isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group>

[0069] As the isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group used in the present invention (hereinafter also referred to as component (A-2)), for example, ER641, ER661 (produced by Seiko PMC Co., Ltd.), UNISTOLE P801, P802 (produced by Mitsui Chemicals, Inc.), SURFLEN P1000 (produced by Mitsubishi Chemical Corporation), etc., can be mentioned. The isobutylene polymer having a carboxylic acid group is obtained, for example, by graft-modifying an isobutylene polymer under free radical reaction conditions. As the carboxylic anhydride group, for example, a group derived from succinic anhydride, a group derived from maleic anhydride, a group derived from glutaric anhydride, etc. can be mentioned. The carboxylic anhydride group may have one or more types. The isobutylene polymer having a carboxylic anhydride group is obtained, for example, by graft-modifying an isobutylene polymer with an unsaturated compound having a carboxylic anhydride group under free radical reaction conditions. In addition, the unsaturated compound having a carboxylic anhydride group can also be free radical copolymerized with the isobutylene polymer.

[0070] The concentration of the carboxylic acid group and / or carboxylic acid anhydride group in the isobutylene polymer having the carboxylic acid group and / or carboxylic acid anhydride group is preferably 0.05 to 10 mmol / g, more preferably 0.1 to 5 mmol / g. The concentration of the carboxylic acid group and / or carboxylic acid anhydride group is obtained by defining the acid value as the number of mg of potassium hydroxide required to neutralize the acid present in 1 g of the resin according to JIS K2501.

[0071] The number average molecular weight of the isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group is preferably from 1,000 to 150,000, more preferably from 10,000 to 100,000, particularly preferably from 30,000 to 80,000, from the viewpoint of bending resistance and the like.

[0072] <(B) Plasticizer>

[0073] In order to further improve the responsiveness to deformation and the adhesiveness, etc., the adhesive composition of the present invention contains a plasticizer (hereinafter also referred to as component (B)). From the viewpoint of exerting the function as a plasticizer, the plasticizer used in the present invention is a plasticizer that is liquid at 25°C and has a viscosity of less than 10000 mPa·s at 25°C. The viscosity of the plasticizer is preferably 5000 mPa·s or less, more preferably 2000 mPa·s or less, and further preferably 1000 mPa·s or less. As plasticizers, for example, plasticizers of phthalates, adipic acid esters, phosphates, trimellitic acid esters, sulfonic acid esters, petroleum oils, liquid polyolefins, liquid polybutadiene, polyol polyesters, animal oils, vegetable oils, etc. can be cited. Two or more plasticizers can be used in combination. It should be noted that the viscosity of the plasticizer in the present invention can be measured using a vibration viscometer or an E-type viscometer. In this case, the vibration viscometer is suitable for measuring the viscosity of plasticizers in a relatively low viscosity range (e.g., 1000 mPa·s or less). Commercially available viscometers include, for example, a vibration viscometer manufactured by SEKONIC Co., Ltd. (trade name: VISCOMATE MODEL VM-10A), an E-type viscometer manufactured by TOKI SANGYO CO., LTD. (trade name: RE85H), and the like.

[0074] Phthalate plasticizers include, for example, dioctyl phthalate (DOP), dibutyl phthalate (DBP), etc. Adipate plasticizers include, for example, dioctyl adipate, propylene glycol adipate polyester, butylene glycol adipate polyester, etc. Phosphate plasticizers include, for example, tricresyl phosphate, trioctyl phosphate, etc. Trimellitate plasticizers include, for example, trioctyl trimellitate, etc. Sulfonate plasticizers include, for example, alkyl sulfonates, etc.

[0075] Examples of petroleum oils include paraffin oil (liquid paraffin), naphthenic oil, aromatic oil, etc. Examples of liquid polyolefins include liquid polybutene, ethylene-α-olefin cooligomers, etc. Examples of polyol polyesters include diethylene glycol dibenzoate, pentaerythritol esters, etc.

[0076] Examples of animal oils include squalane and squalene, and examples of vegetable oils include olive oil, camellia oil, castor oil, tall oil, peanut oil, cottonseed oil, rapeseed oil, soybean oil, palm oil, and coconut oil.

[0077] Examples of commercially available plasticizers include mesamoll (manufactured by LANXESS), mesamoll2 (manufactured by LANXESS), BXA-N (manufactured by Daihachi Chemical Industry Co., Ltd.), Sanso Cizer DOA (manufactured by Shin Nippon Rika Co., Ltd.), Sanso Cizer DINA (manufactured by Shin Nippon Rika Co., Ltd.), and Sanso Cizer DIDA (manufactured by Shin Nippon Rika Co., Ltd.).

[0078] Examples of commercially available castor oil derivatives include hydrogenated castor oil A (trade name), CO-FA (trade name), DCO-FA (trade name), RIC-CIZER S4 (trade name), RIC-CIZER C-101 (trade name), and RIC-CIZER GR-310 (trade name) manufactured by Ito Oil Manufacturing Co., Ltd., and BLAUNON BR-410 (trade name), BLAUNON BR-410 (trade name), BLAUNON BR-430 (trade name), BLAUNON BR-450 (trade name), BLAUNON CW-10 (trade name), BLAUNON RCW-20 (trade name), BLAUNON RCW-40 (trade name), BLAUNON RCW-50 (trade name), and BLAUNON GR-510 (trade name) manufactured by Aoki Oil & Fats Industries, Ltd. RCW-60 (trade name), and CASTER manufactured by NOF Corporation WAX (カスターワックス)A (trade name), NEWCIZER (ニューサイザー) 510R (trade name), stearic acid SAKURA (ステアリン acid さくら) ( Trade name), castor hydrogenated fatty acid (Bamasu hardened fatty acid) (trade name), NAA-34 (trade name), NAA-160 (trade name), and NAA-175 (trade name), etc.

[0079] As the plasticizer used in the present invention, a phthalate plasticizer is preferred, and dioctyl phthalate is particularly preferred. In addition, as the phthalate plasticizer, from the viewpoint of adhesion, a plasticizer with a low molecular weight is preferred, and the weight average molecular weight is preferably in the range of 200 to 3000, and more preferably 300 to 1000. It should be noted that, herein, "liquid" refers to the state of the plasticizer at room temperature (25°C).

[0080] The content of component (B) in the adhesive composition of the present invention is not particularly limited. From the viewpoint of mechanical properties such as tensile strength, relative to 100% by mass of the non-volatile component of the adhesive composition, it is preferably less than 50% by mass, more preferably less than 40% by mass, and further more preferably less than 30% by mass. On the other hand, from the viewpoint of improving viscosity, relative to 100% by mass of the non-volatile component of the adhesive composition, its content is preferably more than 2% by mass, more preferably more than 4% by mass, further more preferably more than 5% by mass, and particularly preferably more than 10% by mass.

[0081] In one embodiment of the present invention, the content of the component (B) in the adhesive composition of the present invention is preferably 5 to 30% by mass, more preferably 10 to 25% by mass, relative to 100% by mass of the non-volatile components of the adhesive composition. In another embodiment of the present invention, the content of the component (B) in the adhesive composition of the present invention is preferably 10 to 45% by mass, relative to 100% by mass of the non-volatile components of the adhesive composition.

[0082] <(C) Liquid polyolefin and / or liquid rubber>

[0083] For the purpose of further improving adhesion, etc., the adhesive composition of the present invention contains a liquid polyolefin and / or a liquid rubber (hereinafter also referred to as component (C)). As the liquid polyolefin and / or liquid rubber used in the present invention, a substance that does not react with component (A) or a component constituting component (A) (for example, the above-mentioned component (A-1) (isobutylene polymer having an epoxy group), component (A-2) (isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group), etc.) (i.e., a substance that does not have a functional group that reacts with an epoxy group, a carboxylic acid group, or a carboxylic anhydride group) is used. In addition, component (C) is a substance that is liquid at 25°C and has a viscosity of 10 Pa·s (10000 mPa·s) or more, which is obtained by dividing the dynamic viscosity measured by a dynamic viscoelasticity measuring device at 25°C by the density. The viscosity of the component (C) is preferably 20 Pa·s or more, more preferably 50 Pa·s or more, further preferably 100 Pa·s or more, further preferably 500 Pa·s or more, and further preferably 1000 Pa·s or more. Examples of the component (C) include synthetic liquid oil, rubber of C5 petroleum raw material fraction polymer, polybutene, polyisobutylene, polyisoprene, polypropylene, polyterpene, polybutadiene, or copolymers and hydrogenated derivatives thereof. The component (C) preferably has a weight average molecular weight (Mw) of 2000 to 150000, and more preferably has a weight average molecular weight (Mw) of 10000 to 50000. It should be noted that the weight average molecular weight in the present invention is measured by gel permeation chromatography. The dynamic viscosity of the component (C) is measured by a dynamic viscoelasticity measuring device. Examples of commercially available dynamic viscoelasticity measuring devices include a rheometer manufactured by TA Instruments (trade name: DISCOVERY HR-2).

[0084] Synthetic liquid oils are low viscosity oligomers of monoolefins, isoparaffins or paraffins that are always in liquid form. Examples of commercially available liquid polybutene, polyisobutylene, polyisoprene, and polybutadiene include polyisoprene available as LIR30 and LIR50 from Kuraray Co., Ltd., hydrogenated polyisoprene available as LIR290, polybutene available as INDOPOL H-1500, H-1900, H-2100, H-6000, and H-18000 from Ineos, polybutene available as Nippon Polybutene HV-300, HV-1900, and SV-7000 from JXTG Energy Group, polyisobutylene available as OPPANOL B10, B12, B14, and B15 from BASF, and polybutadiene available as B-3000 and BI-3000 from Nippon Soda Co., Ltd.

[0085] The content of component (C) in the adhesive composition of the present invention is not particularly limited. From the viewpoint of the tendency of component (C) to reduce the deformation recovery rate and the viewpoint of maintaining the deformation recovery rate, relative to 100 mass % of the non-volatile components of the adhesive composition, it is preferably below 40 mass %, more preferably below 35 mass %, and further preferably below 25 mass %. On the other hand, from the viewpoint of maintaining adhesion, relative to 100 mass % of the non-volatile components of the adhesive composition, its content is preferably above 5 mass %, more preferably above 7 mass %, and further preferably above 10 mass %.

[0086] In one embodiment of the present invention, the content of the component (C) in the adhesive composition of the present invention is preferably 5 to 40% by mass, more preferably 10 to 25% by mass, relative to 100% by mass of the non-volatile components of the adhesive composition. In another embodiment of the present invention, the content of the component (C) in the adhesive composition of the present invention is preferably 10 to 45% by mass, relative to 100% by mass of the non-volatile components of the adhesive composition.

[0087] <(D) Curing agent and / or curing accelerator>

[0088] From the viewpoint of improving the curing performance of the adhesive composition, the adhesive composition of the present invention may further include a curing agent and / or a curing accelerator (hereinafter also referred to as component (D)). Two or more components (D) may be used in combination. Even if the component (D) is the same compound, it may function as a curing agent or as a curing accelerator depending on the system.

[0089] Examples of the curing agent in the component (D) include ionic liquids, imidazole compounds, tertiary amine compounds, dimethyl urea compounds, amine addition compounds, organic acid dihydrazide compounds, organic phosphine compounds, dicyandiamide compounds, primary amine compounds, secondary amine compounds, phenol compounds, thiol compounds, etc. Examples of the curing accelerator in the component (D) include ionic liquids, imidazole compounds, tertiary amine compounds, dimethyl urea compounds, amine addition compounds, organic phosphine compounds, quaternary ammonium salts, etc.

[0090] Examples of the ionic liquid as a curing agent and / or a curing accelerator in the present invention include those described in JP-A-2016-186843. Specific examples of the ionic liquid include 1-butyl-3-methylimidazolium lactate, tetrabutylphosphonium-2-pyrrolidone-5-carboxylate, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium trifluoroacetate, tetrabutylphosphonium α-lipoate, tetrabutylphosphonium formate, tetrabutylphosphonium lactate, bis(tetrabutylphosphonium) tartrate, tetrabutylphosphonium hippurate, tetrabutylphosphonium N-methylhippurate, tetrabutylphosphonium benzoyl-DL-alanine, tetrabutylphosphonium N-acetylphenylalanine, tetrabutylphosphonium 2,6-di-tert-butylphenol, monotetrabutylphosphonium L-aspartate, tetrabutylphosphonium glycine, tetrabutylphosphonium N-acetylglycine, 1- Ethyl-3-methylimidazolium lactate, 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium formate, 1-ethyl-3-methylimidazolium hippurate, 1-ethyl-3-methylimidazolium N-methylhippurate, bis(1-ethyl-3-methylimidazolium)tartrate, 1-ethyl-3-methylimidazolium N-acetylglycine, etc., preferably tetrabutylphosphonium decanoate, tetrabutylphosphonium N-acetylglycine, 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium formate, 1-ethyl-3-methylimidazolium hippurate, 1-ethyl-3-methylimidazolium N-methylhippurate.

[0091] As for the imidazole compound used as the curing agent and / or curing accelerator in the present invention, for example, 1H-imidazole, 2-methylimidazole, 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 2,4-diamino-6-(2'-undecylimidazolyl-(1'))-ethyl-s-triazine, 2-phenyl-4,5-bis((2'-undecylimidazolyl)-triazine) and 2,4-diamino-6-(2'-undecylimidazolyl-(1'))-ethyl-s-triazine are mentioned. hydroxymethyl) imidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 2-phenylimidazole, 2-dodecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,4-diamino-6-(2'-methylimidazolyl-(1')-ethyl-s-triazine, 2,4-diamino-6-(2'-methylimidazolyl-(1'))-ethyl-s-triazine isocyanuric acid adduct, etc. Specific examples of imidazole compounds include Curezol 2MZ, 2P4MZ, 2E4MZ, 2E4MZ-CN, C11Z, C11Z-CN, C11Z-CNS, C11Z-A, 2PHZ, 1B2MZ, 1B2PZ, 2PZ, C17Z, 1.2DMZ, 2P4MHZ-PW, 2MZ-A, 2MA-OK (all manufactured by Shikoku Chemical Industry Co., Ltd.), etc.

[0092] Regarding the tertiary amine compound used as the curing agent and / or curing accelerator in the present invention, for example, DBN (1,5-diazabicyclo[4.3.0]non-5-ene), DBU (1,8-diazabicyclo[5.4.0]undec-7-ene), 2-ethylhexanoate of DBU, phenolate of DBU, p-toluenesulfonate of DBU, U-CAT SA 102 (manufactured by San-Apro: octanoate of DBU), DBU formate and other DBU-organic acid salts, 2,4,6-tris(dimethylaminomethyl)phenol (TAP), etc.

[0093] As for the dimethyl urea compound used as the curing agent and / or curing accelerator in the present invention, for example, there can be mentioned aromatic dimethyl ureas such as DCMU (3-(3,4-dichlorophenyl)-1,1-dimethyl urea), U-CAT3512T (manufactured by San-Apro Co., Ltd.), and aliphatic dimethyl ureas such as U-CAT3503N (manufactured by San-Apro Co., Ltd.). Among them, aromatic dimethyl ureas are preferably used from the viewpoint of curability.

[0094] As for the amine addition compound used as the curing agent and / or curing accelerator in the present invention, for example, an epoxy addition compound obtained by stopping the addition reaction of a tertiary amine on an epoxy resin midway, etc. Specific examples of the amine addition compound include: Ajicure PN-23, Ajicure MY-24, Ajicure PN-D, Ajicure MY-D, Ajicure PN-H, Ajicure MY-H, Ajicure PN-31, Ajicure PN-40, Ajicure PN-40J (all manufactured by Ajinomoto Fine-Techno Co., Ltd.), etc.

[0095] Examples of the organic acid dihydrazide compound as the curing agent in the present invention include Ajicure VDH-J, Ajicure UDH, and Ajicure LDH (all manufactured by Ajinomoto Fine-Techno Co., Ltd.).

[0096] As for the organic phosphine compound used as the curing agent and / or curing accelerator in the present invention, for example, triphenylphosphine, tetraphenylphosphonium tetra-p-tolyl borate, tetraphenylphosphonium tetraphenyl borate, tri-tert-butylphosphonium tetraphenyl borate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, triphenylphosphine triphenylborane, etc. Specific examples of the organic phosphine compound include TPP, TPP-MK, TPP-K, TTBuP-K, TPP-SCN, TPP-S (manufactured by Hokuko Chemical Industry Co., Ltd.), etc.

[0097] The dicyandiamide compound used as the curing agent in the present invention includes, for example, dicyandiamide. Specific examples of the dicyandiamide compound include DICY7 and DICY15 (both manufactured by Mitsubishi Chemical Corporation), which are finely ground dicyandiamide.

[0098] As primary amine compounds and secondary amine compounds used as curing agents in the present invention, for example, aliphatic amines such as diethylenetriamine, triethylenetetramine, tetraethylenepentamine, trimethylhexamethylenediamine, 2-methylpentamethylenediamine, 1,3-bisaminomethylcyclohexane, propylenediamine, diethylaminopropylamine, bis(4-aminocyclohexyl)methane, norbornene diamine, and 1,2-diaminocyclohexane; alicyclic amines such as N-aminoethylpiperazine and 1,4-bis(3-aminopropyl)piperazine; and aromatic amines such as diaminodiphenylmethane, metaphenylenediamine, metaxylene diamine, metaphenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone, and diethyltoluenediamine. Specific examples of primary amine compounds and secondary amine compounds include KAYAHARD AA (manufactured by Nippon Kayaku Co., Ltd.: 4,4'-diamino-3,3'-dimethyldiphenylmethane).

[0099] As for the phenolic compound used as the curing agent in the present invention, for example, phenolic curing agents containing a triazine skeleton, phenol novolac curing agents containing a triazine skeleton, MEH-7700, MEH-7810, MEH-7851 (manufactured by Meiwa Chemicals Co., Ltd.), NHN, CBN, GPH (manufactured by Nippon Kayaku Co., Ltd.), SN170, SN180, SN190, SN475, SN485, SN495, SN375, SN395 (manufactured by Tohto Chemicals Co., Ltd.), TD2090 (manufactured by DIC Corporation), etc. As specific examples of phenolic curing agents containing a triazine skeleton, LA3018 (manufactured by DIC Corporation) etc. As specific examples of phenolic curing agents containing a triazine skeleton, LA7052, LA7054, LA1356 (manufactured by DIC Corporation) etc. can be mentioned.

[0100] Examples of the thiol compound used as the curing agent in the present invention include trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptopropionate), dipentaerythritol hexa(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, tris(3-mercaptopropyl)isocyanurate, 1,4-bis(3-mercaptobutyryloxy)butane, 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and 1,3,4,6-tetrakis(2-mercaptoethyl)glycoluril. Commercially available products include OTG, EGTG, TMTG, PETG, 3-MPA, TMTP, and PETP manufactured by Yodo Chemical Co., Ltd., TEMP, PEMP, TEMPIC, and DPMP manufactured by Sakai Chemical Industry Co., Ltd., PE-1, BD-1, NR-1, TPMB, and TEMB manufactured by Showa Denko K.K., and TS-G manufactured by Shikoku Chemical Industry Co., Ltd.

[0101] Regarding the quaternary ammonium salt as a curing accelerator in the present invention, for example, tetraalkylammonium salts (each alkyl group has 1 to 18 carbon atoms) [for example, tetraethylammonium bromide, tetrabutylammonium bromide, tetraalkylammonium carboxylates (carboxylic acid has 1 to 12 carbon atoms)], aromatic ring-containing quaternary ammonium salts [for example, benzyltriphenylammonium carboxylate, etc.], etc. can be mentioned.

[0102] In the adhesive composition of the present invention, when a curing agent and / or curing accelerator as component (D) is included, the content of component (D) is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, further preferably 0.1% by mass or more, and particularly preferably 0.2% by mass or more relative to 100% by mass of the non-volatile component of the adhesive composition. In addition, the content of component (D) is preferably 10% by mass or less, more preferably 8% by mass or less, further preferably 5% by mass or less, and particularly preferably 3% by mass or less.

[0103] In one embodiment of the present invention, the content of the component (D) in the adhesive composition of the present invention is preferably from 0.1 to 10 mass %, more preferably from 0.2 to 8 mass %, based on 100 mass % of the nonvolatile components in the adhesive composition.

[0104] <(E) Adhesiveness-imparting agent>

[0105] In the adhesive composition of the present invention, in order to further improve the purpose of adhesion, etc., an adhesion-imparting agent (hereinafter also referred to as (E) component) may be included. The adhesion-imparting agent is also called a tackifier, and examples thereof include terpene resins, rosin resins, alicyclic hydrocarbon resins, aliphatic hydrocarbon resins, aliphatic / aromatic copolymer hydrocarbon resins, aromatic hydrocarbon resins, coumarone / indene resins, etc. The adhesion-imparting agent may be used in combination of two or more. As a more preferred adhesion-imparting agent, an aliphatic / aromatic copolymer hydrocarbon resin, an aromatic hydrocarbon resin, a coumarone / indene resin, etc. may be mentioned.

[0106] When using (E) component, the content of (E) component in the adhesive composition of the present invention is not particularly limited. From the viewpoint of not hindering the characteristics of the rubber of (A) component, relative to 100% by mass of the non-volatile component of the adhesive composition, it is preferably below 35% by mass, more preferably below 30% by mass, and further preferably below 25% by mass. On the other hand, from the viewpoint of the improvement of peel strength, relative to 100% by mass of the non-volatile component of the adhesive composition, its content is preferably above 2% by mass, more preferably above 4% by mass, further preferably above 5% by mass, and particularly preferably above 6% by mass.

[0107] In one embodiment of the present invention, the content of the component (E) in the adhesive composition of the present invention is preferably 5 to 30 mass %, more preferably 6 to 25 mass %, based on 100 mass % of the nonvolatile matter in the adhesive composition.

[0108] Examples of commercially available tackifiers include ARKON P-90 (manufactured by Arakawa Chemical Industries, Ltd.), ARKON P-100 (manufactured by Arakawa Chemical Industries, Ltd.), ARKON P-115 (manufactured by Arakawa Chemical Industries, Ltd.), Pine Crystal ME-G (manufactured by Arakawa Chemical Industries, Ltd.), Pine Crystal ME-H (manufactured by Arakawa Chemical Industries, Ltd.), Pine Crystal ME-G (manufactured by Arakawa Chemical Industries, Ltd.), T-REZ RB093 (manufactured by JXTG Energy Group), T-REZ RC115 (manufactured by JXTG Energy Group), Neopolymer L90 (manufactured by JXTG Energy Group), Neopolymer 120 (manufactured by JXTG Energy Group), Neopolymer 140 (manufactured by JXTG Energy Group), T-REZ HA-105 (manufactured by JXTG Energy Group), Petcoal 120 (manufactured by Tosoh Corporation), Petrotack 90HS (manufactured by Tosoh Corporation), Petrotack 100V (manufactured by Tosoh Corporation), Novares (ノバレス) C9 (ノバレス・ルトガース Corporation), Novares L (manufactured by Nippon Chemical Co., Ltd.), NITTORESIN (manufactured by Nippon Chemical Co., Ltd.), NITTORESIN G-90 (manufactured by Nippon Chemical Co., Ltd.), etc.

[0109] <Other ingredients>

[0110] The adhesive composition of the present invention may further contain other additives different from the above-mentioned components. Such additives include, for example, inorganic fillers such as silicon dioxide, aluminum oxide, barium sulfate, talc, clay, mica powder, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, boron nitride, aluminum borate, barium titanate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, barium zirconate, and calcium zirconate, hygroscopic metal oxides such as calcium oxide, magnesium oxide, strontium oxide, aluminum oxide, barium oxide, calcined dolomite (a mixture containing calcium oxide and magnesium oxide), calcined hydrotalcite (a composite oxide of aluminum and magnesium), and semi-calcined hydrotalcite, organic fillers such as rubber particles, silicon powder, nylon powder, and fluororesin powder, thickeners such as Orben and Benton, silicone-based, fluorine-based, and polymer-based defoamers or leveling agents, and adhesion-imparting agents such as triazole compounds, thiazole compounds, triazine compounds, and porphyrin compounds. The inorganic filler or hygroscopic metal oxide can be surface treated with a surface treatment agent to improve its moisture resistance. As the surface treatment agent, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, vinylsilane coupling agents, imidazole silane coupling agents, organic silazane compounds, titanate coupling agents, etc. can be cited. These can be used alone or in combination of two or more.

[0111] The present invention also relates to an adhesive composition before component (A) forms a crosslinked structure. That is, the present invention also relates to an adhesive composition comprising: (A') an isobutylene polymer (one or more) having a functional group capable of forming a crosslinked structure, (A") an isobutylene polymer (one or more) having a functional group capable of reacting with the functional group of the isobutylene polymer having a crosslinked structure to form a crosslinked structure and / or a crosslinking agent (one or more), (B) a plasticizer, and (C) a liquid polyolefin and / or a liquid rubber. As a preferred form of the adhesive composition before component (A) forms a crosslinked structure, an adhesive composition comprising:

[0112] (A-1) an isobutylene polymer having an epoxy group,

[0113] (A-2) an isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group,

[0114] (B) plasticizers, and

[0115] (C) Liquid polyolefin and / or liquid rubber.

[0116] The adhesive composition of the present invention may contain an organic solvent. In particular, when the adhesive composition before the component (A) forms a crosslinked structure is made into a varnish in order to prepare an adhesive sheet having an adhesive composition layer formed on a support body described later, an organic solvent may be added from the viewpoint of the coating property of the adhesive composition. Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone (hereinafter also referred to as "MEK"), and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and the like. The organic solvent may be used alone or in combination of two or more. The amount of the organic solvent is not particularly limited, but from the viewpoint of coating property, it is preferably used in an amount such that the viscosity (25° C.) of the adhesive composition reaches 300 to 2000 mPa·s. The adhesive composition of the present invention can be produced by mixing the components using a kneading roll, a rotary mixer or the like.

[0117] The adhesive sheet of the present invention can be manufactured by applying a varnish-like adhesive composition on a support and heating and drying it to form an adhesive composition layer, in which a cross-linked structure is formed. A preferred form of the method for manufacturing the adhesive sheet of the present invention includes the following steps: applying a varnish-like adhesive composition in an adhesive composition containing the above-mentioned (A') isobutylene polymer having a functional group capable of forming a cross-linked structure, (A") an isobutylene polymer and / or a cross-linking agent having a functional group capable of reacting with the functional group of the isobutylene polymer having a cross-linked structure to form a cross-linked structure, (B) a plasticizer, and (C) a liquid polyolefin and / or liquid rubber to form a cross-linked structure. As a more preferred embodiment, the method comprises the following steps: applying the adhesive composition in a varnish state before the component (A) forms a crosslinked structure, which contains the above-mentioned components (A-1), (A-2), (B) and (C), on a support and heating and drying the adhesive composition, and forming an adhesive composition layer having a crosslinked structure by reaction between the epoxy group of the component (A-1) and the carboxylic acid group and / or carboxylic anhydride group of the component (A-2).

[0118] As mentioned above, a varnish-like adhesive composition is applied to a support, and the resulting coating is dried by heating or hot air blowing, etc., to obtain a sheet having an adhesive composition layer (a cross-linked structure is formed in the adhesive composition layer) formed on the support, i.e., an adhesive sheet. From the viewpoint of the balance between light absorption performance and transmittance, the thickness of the adhesive composition layer in the adhesive sheet is preferably 5 μm to 200 μm, more preferably 15 to 180 μm, and further preferably 20 μm to 150 μm.

[0119] The support for the adhesive sheet is not particularly limited, and examples thereof include polyolefins such as polyethylene, polypropylene, and polyvinyl chloride, polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate, polycarbonate, and plastic films of polyimide. PET is particularly preferred as the plastic film. In addition, the support may also be a metal foil such as aluminum foil, stainless steel foil, and copper foil.

[0120] In the case where a moisture-proof layer is provided on the device, a moisture-proof support (moisture-proof support) can be used as a support for the adhesive sheet. In addition, in the case where a layer of a circular polarizer is provided on the device, a circular polarizer can be used as a support for the adhesive sheet. In addition, in the case where a moisture-proof layer and a layer of a circular polarizer are provided on the device, a support comprising both a moisture-proof support and a circular polarizer can be used as a support for the adhesive sheet.

[0121] As a moisture-proof support, there can be mentioned a moisture-proof plastic film, or a metal foil such as copper foil, aluminum foil, etc. As a moisture-proof plastic film (barrier film), there can be mentioned a plastic film obtained by vapor-depositing inorganic substances such as silicon oxide (silicon dioxide), silicon nitride, SiCN, amorphous silicon, etc. on the surface. Here, as a plastic film on which an inorganic substance is vapor-deposited on the surface, preferably, for example, a plastic film of polyolefin (for example, polyethylene, polypropylene, polyvinyl chloride, etc.), polyester (for example, polyethylene terephthalate (hereinafter sometimes referred to as "PET"), polyethylene naphthalate, polycarbonate, polyimide, etc., is particularly preferred, and a PET film is particularly preferred. Examples of commercially available moisture-proof plastic films include: TECHBARRIER HX, AX, LX, L series (manufactured by Mitsubishi Chemical Corporation), TECHBARRIER HX, AX, LX, L series further improve the moisture-proof effect of X-BARRIER (Mitsubishi Chemical Corporation system) etc. In addition, as a support with moisture resistance, a support with a multilayer structure of more than 2 layers can be used, for example, a support obtained by bonding the above-mentioned plastic film and the above-mentioned metal foil with an adhesive. The support is cheap and is also advantageous from the viewpoint of handleability. It should be noted that the support of the adhesive sheet can also use a support that does not have moisture resistance (for example, a monomer of the above-mentioned plastic film on which inorganic substances are not evaporated on the surface).

[0122] Usually, circular polarizer is made of polarizer and 1 / 4 wave plate.When circular polarizer is used as support, usually, 1 / 4 wave plate is configured on the bonding composition layer side.In addition, when using a support comprising a circular polarizer and a moisture-proof support, it is better to configure the moisture-proof support on the bonding composition layer side, and configure the 1 / 4 wave plate of circular polarizer on the moisture-proof support side.Moisture-proof support and circular polarizer can be bonded by adhesive etc.

[0123] The support may be subjected to matte treatment, corona treatment, and demolding treatment in advance. That is, the support may be a releasable support. As demolding treatment, demolding treatment using a release agent such as a silicone resin release agent, an alkyd resin release agent, or a fluororesin release agent may be cited. In the present invention, when the support has a demolding layer, the demolding layer is also regarded as a part of the support. The thickness of the support is not particularly limited, but from the viewpoint of operability, it is preferably 20 to 200 μm, and more preferably 20 to 125 μm.

[0124] In the adhesive sheet, the adhesive composition layer can be protected by a protective film. By protecting with a protective film, it is possible to prevent garbage from being attached to the surface of the adhesive composition layer or forming damage. The protective film is preferably a plastic film similar to the support. In addition, the protective film can also be pre-treated with matte, corona treatment, and demoulding. The thickness of the protective film is not particularly limited, and is usually 1 to 150 μm, preferably 10 to 100 μm.

[0125] <Electronic devices>

[0126] For the flexible electronic device of the present invention, for example, when the adhesive sheet of the present invention is a sealing sheet, it can be manufactured by laminating the adhesive sheet of the present invention on the electronic element on the substrate. In addition, in the manufacturing process of the flexible electronic device, when laminating multiple materials, the adhesive sheet of the present invention can be used as an interlayer adhesive. For example, in the case of a flexible display, the adhesive sheet of the present invention can be used as an interlayer adhesive to laminate a touch screen sensor, a polarizer, a surface protection sheet, etc.

[0127] Example

[0128] The present invention is described in more detail below with reference to the following examples. The present invention is not limited to the following examples, and can be implemented with appropriate changes within the scope of the subject matter of the context, all of which are included in the technical scope of the present invention. It should be noted that, unless otherwise specified, "parts" and "%" in the amount of components and copolymerization units refer to "parts by mass" and "% by mass", respectively.

[0129] The materials used in the examples and comparative examples are as follows;

[0130] (A-1)Ingredients

[0131] "ER850" glycidyl methacrylate modified butyl rubber (GMA modified butyl) (produced by Seiko PMC Co., Ltd.), epoxy group concentration 0.64 mmol / g, number average molecular weight 110000

[0132] (A-2)Ingredients

[0133] “ER641” maleic anhydride-modified butyl rubber (MA-modified butyl) (manufactured by Seiko PMC Co., Ltd.), anhydride group concentration of 0.46 mmol / g, number average molecular weight of 57,000.

[0134] (B) Ingredients

[0135] "DOP" phthalic acid plasticizer (dioctyl phthalate) (manufactured by J-PLUS Co., Ltd.), liquid at 25°C, viscosity 73 mPa·s at 25°C

[0136] "DIDA" adipic acid plasticizer (diisodecyl adipate) (manufactured by J-PLUS Co., Ltd.), liquid at 25°C, viscosity 35 mPa·s at 25°C

[0137] "LX-004" liquid polyalphaolefin (ethylene-alpha olefin co-oligomer) (Mitsui Chemicals, Inc.), liquid at 25°C, viscosity at 25°C 727 mPa·s

[0138] "LV-50" polybutene (manufactured by JX Energy Co., Ltd.) is liquid at 25°C and has a viscosity of 223 mPa·s at 25°C.

[0139] The viscosity of the component (B) was measured using a vibration viscometer manufactured by SEKONIC CORPORATION (trade name: VISCOMATE MODEL VM-10A).

[0140] (C) Ingredients

[0141] Oppanol B10 polyisobutylene (produced by BASF), weight average molecular weight 40,000, liquid at 25°C, viscosity 21,000 Pa·s at 25°C

[0142] "LIR-290" hydrogenated polyisoprene (manufactured by Kuraray Co., Ltd.), weight average molecular weight 31,000, liquid at 25°C, viscosity 1,400 Pa·s at 25°C

[0143] The viscosity of the component (C) was calculated by dividing the dynamic viscosity at 25° C. measured using a rheometer manufactured by TA Instruments (trade name: DISCOVERY HR-2) by the density of each component (C).

[0144] (D) Ingredients

[0145] “SA102” DBU type curing accelerator (manufactured by San-Apro Co., Ltd.).

[0146] Other Ingredients

[0147] “Butyl 065” butyl rubber (manufactured by JSR Corporation).

[0148] Each composition of Examples and Comparative Examples was prepared by the following procedure. The components were blended in the amounts shown in Table 1. The amounts of components other than the organic solvent described in Table 1 are values ​​converted to non-volatile components.

[0149] <Example 1>

[0150] 114 parts (40 parts in terms of non-volatile components) of maleic anhydride (MA)-modified butyl rubber (ER641, 35% Ipzole solution), 30 parts of phthalate (DOP), 50 parts (25 parts in terms of non-volatile components) of polyisobutylene (Oppanol B10, 50% Ipzole solution) and 5 parts (1 part in terms of non-volatile components) of a DBU-based curing accelerator (SA102, 20% toluene solution) were mixed into 125 parts (25 parts in terms of non-volatile components) of glycidyl methacrylate (GMA)-modified butyl rubber (ER850, 20% Ipzole solution), and the resulting mixture was uniformly dispersed using a high-speed rotary mixer to obtain a varnish of an adhesive composition. The obtained varnish was uniformly applied on a release-treated surface of a PET film (38 μm thick) treated with a silicone-based release agent using a die coater and heated at 130° C. for 30 minutes to obtain an adhesive sheet having an adhesive composition layer of 25 μm thickness.

[0151] <Example 2>

[0152] A varnish of an adhesive composition and an adhesive sheet were prepared in the same manner as in Example 1 except that adipic acid ester (DIDA) was used instead of phthalic acid ester (DOP).

[0153] <Example 3>

[0154] A varnish of an adhesive composition and an adhesive sheet were prepared in the same manner as in Example 1 except that an ethylene-α-olefin co-oligomer (LX-004) was used instead of phthalate (DOP).

[0155] <Example 4>

[0156] A varnish of an adhesive composition and an adhesive sheet were prepared in the same manner as in Example 1 except that polybutene (LV-50) was used instead of phthalate (DOP).

[0157] <Example 5>

[0158] A varnish of an adhesive composition and an adhesive sheet were prepared in the same manner as in Example 1 except that polyisoprene (LIR-290) was used instead of polyisobutylene (Oppanol B10).

[0159] <Comparative Example 1>

[0160] A varnish of an adhesive composition and an adhesive sheet were prepared in the same manner as in Example 1 except that polyisobutylene (Oppanol B10) was not used.

[0161] <Comparative Example 2>

[0162] A varnish of an adhesive composition and an adhesive sheet were prepared in the same manner as in Example 1 except that no phthalate (DOP) was used.

[0163] <Comparative Example 3>

[0164] A varnish of an adhesive composition and an adhesive sheet were prepared in the same manner as in Example 1 except that phthalate (DOP) and polyisobutylene (Oppanol B10) were not used.

[0165] <Comparative Example 4>

[0166] 30 parts of phthalate (DOP) and 50 parts of polyisobutylene (Oppanol B10, 50% Ipzole solution) were mixed with 433 parts (65 parts in terms of nonvolatile components) of butyl rubber (Butyl 065, 15% Ipzole solution), and the resulting mixture was uniformly dispersed using a high-speed rotary mixer to obtain a varnish of an adhesive composition. The resulting varnish was uniformly applied to a release-treated surface of a PET film (38 μm thick) treated with a silicone-based release agent using a die coater, and heated at 130° C. for 30 minutes to obtain an adhesive sheet having an adhesive composition layer with a thickness of 25 μm.

[0167] Whether a cross-linked structure is formed in the adhesive sheets of the examples and comparative examples obtained as described above was confirmed as follows. About 1 g of the adhesive sheet was collected and accurately weighed. Then, the accurately weighed adhesive sheet was immersed in 40 g of toluene for 7 days, and then all the toluene-insoluble components of the adhesive composition were recovered, and dried at 130°C for 2 hours to obtain the dry mass. Next, the gel fraction of the adhesive component was calculated according to the following formula;

[0168] Gel fraction of adhesive sheet = (dry mass of toluene insoluble component / mass of adhesive sheet before immersion) × 100

[0169] When the gel fraction determined by the above test is 10% or more, it is considered that a cross-linked structure is formed, and it was confirmed that a cross-linked structure was formed in Examples and Comparative Examples other than Comparative Example 4.

[0170] The adhesive composition layers of the adhesive sheets of Examples and Comparative Examples obtained as described above were evaluated as follows.

[0171] <Evaluation of responsiveness and recovery to deformation>

[0172] The following test evaluated the responsiveness and recovery properties to the deformation generated when stress was applied to the adhesive composition layer.

[0173] An evaluation sample with a diameter of 8 mm and a thickness of about 1.0 mm was fixed to a DHR parallel plate rheometer and loaded with a shear stress of 95 kPa for 5 seconds. The stress was released and the evaluation sample was allowed to recover for 60 seconds using a fixing tool, thereby performing a deformation responsiveness test and a deformation recovery test on the evaluation sample.

[0174] The deformation responsiveness was evaluated based on the peak shear deformation rate when the shear stress of 95 kPa was applied for 5 seconds. In addition, the shear stress of 95 kPa was applied for 5 seconds, the stress applied at this time was released, and the deformation recovery was evaluated based on the deformation recovery rate after 60 seconds.

[0175] The deformation recovery was evaluated by the deformation recovery rate calculated as ((S1-S2) / S1)×100; where S1 is the shear deformation rate recorded at the peak value 5 seconds after the load stress, and S2 is the shear deformation rate measured 60 seconds after the load stress was released.

[0176] <Deformation responsiveness>

[0177] Excellent ○: Deformation rate is 200[%] or more

[0178] Good △: The deformation rate is 100[%] or more and less than 200[%]

[0179] Defective ×: The deformation rate is less than 100 [%].

[0180] <Deformation recovery>

[0181] Excellent ○: Deformation recovery rate is 50% or more

[0182] Good △: Deformation recovery rate is 30% or more and less than 50%

[0183] Defective ×: The deformation recovery rate is less than 30 [%].

[0184] <Evaluation of Adhesion>

[0185] The adhesion of the adhesive composition layer was evaluated by the following test. The adhesive sheets (thickness of the adhesive composition layer: 25 μm) prepared in the examples and comparative examples were cut into a length of 70 mm × a width of 20 mm, and the cut adhesive sheets were laminated to the aluminum surface of the aluminum foil / PET composite film "AL1N30 with PET" (aluminum foil 30 μm, PET 25 μm: Toyo Aluminum Sales Co., Ltd., trade name) with a length of 150 mm × a width of 25 mm using a batch vacuum laminator (V-160 manufactured by Nichigo-Morton Co., Ltd.). The lamination conditions were a temperature of 80°C, a decompression time of 30 seconds, and then pressurization at a pressure of 0.3 MPa for 30 seconds. Then, the PET film of the adhesive sheet was peeled off, and a glass plate (length 76 mm × width 26 mm × thickness 1.2 mm, microscope slide) was laminated on the exposed adhesive composition layer under the same conditions as above to make a laminate. The obtained laminate was measured for peel strength against a glass plate surface when peeled at a tensile rate of 50 mm / min in a direction at 90° to the longitudinal direction of the aluminum foil / PET composite film, and adhesiveness was evaluated according to the following criteria.

[0186] Excellent ○: Peel strength is 0.25 [kgf / cm] or more

[0187] Good △: Peel strength is 0.15 [kgf / cm] or more and less than 0.25 [kgf / cm]

[0188] Defective ×: The peel strength is less than 0.15 [kgf / cm].

[0189] [Table 1]

[0190]

[0191] Possibility of industrial application

[0192] The adhesive sheet of the present invention has high adhesiveness and is excellent in responsiveness and recovery to deformation, and can be preferably used as a sealing sheet, an adhesive sheet, a transparent optical adhesive sheet (OCA), etc. for flexible electronic devices.

[0193] This application is based on Japanese Patent Application No. 2019-180696 filed in Japan, the contents of which are incorporated herein in their entirety.

Claims

1. An adhesive sheet comprising a support and an adhesive composition layer formed on the support, in, The adhesive composition constituting the adhesive composition layer contains: (A) an isobutylene polymer having a cross-linked structure, (B) a plasticizer that is liquid at 25°C and has a viscosity of less than 10,000 mPa·s at 25°C, and (C) a liquid polyolefin and / or liquid rubber which is liquid at 25°C and has a viscosity of 10000 mPa·s or more at 25°C, The isobutylene polymer having a cross-linked structure is a reaction product of an isobutylene polymer having an epoxy group and an isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group. The quantitative ratio of the isobutylene polymer having an epoxy group and the isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group in the reaction is 100:10 to 100:200 in terms of the molar ratio of the epoxy group to the carboxylic acid group and / or the carboxylic anhydride group.

2. The adhesive sheet according to claim 1, wherein The plasticizer is a plasticizer that is liquid at 25°C and has a viscosity of 5000 mPa·s or less at 25°C.

3. The adhesive sheet according to claim 1 or 2, wherein: The liquid polyolefin and / or liquid rubber is a liquid polyolefin and / or liquid rubber which is liquid at 25°C and has a viscosity of 20 Pa·s or more at 25°C.

4. The adhesive sheet according to claim 1 or 2, wherein: The isobutylene-based polymer having a crosslinked structure includes crosslinked bonds formed by the reaction of an epoxy group with a carboxylic acid group and / or a carboxylic anhydride group.

5. The adhesive sheet according to claim 1 or 2, wherein: Isobutylene polymers are copolymers of isobutylene and isoprene.

6. The adhesive sheet according to claim 1 or 2, wherein: The adhesive composition contains 40 to 80% by mass of the isobutylene polymer having a crosslinked structure, based on 100% by mass of the nonvolatile components of the adhesive composition.

7. The adhesive sheet according to claim 6, wherein The adhesive composition contains 40 to 60% by mass of the isobutylene polymer having a crosslinked structure, based on 100% by mass of the nonvolatile components of the adhesive composition.

8. The adhesive sheet according to claim 1 or 2, wherein: The adhesive composition contains 10 to 45% by mass of the plasticizer based on 100% by mass of the nonvolatile components of the adhesive composition.

9. The adhesive sheet according to claim 8, wherein The adhesive composition contains 10 to 25% by mass of the plasticizer based on 100% by mass of the nonvolatile components of the adhesive composition.

10. The adhesive sheet according to claim 1 or 2, wherein The adhesive composition contains 10 to 45% by mass of the liquid polyolefin and / or the liquid rubber based on 100% by mass of the nonvolatile components of the adhesive composition.

11. The adhesive sheet according to claim 10, wherein The adhesive composition contains 10 to 25% by mass of the liquid polyolefin and / or the liquid rubber based on 100% by mass of the nonvolatile components of the adhesive composition. 12 . The adhesive sheet according to claim 1 or 2 , which is used for a flexible electronic device.

13. The adhesive sheet according to claim 12, wherein The flexible electronic device is a flexible organic EL device or a flexible solar cell device.

14. An adhesive composition comprising: (A) an isobutylene polymer having a cross-linked structure, (B) a plasticizer that is liquid at 25°C and has a viscosity of less than 10,000 mPa·s at 25°C, and (C) a liquid polyolefin and / or liquid rubber which is liquid at 25°C and has a viscosity of 10000 mPa·s or more at 25°C, The isobutylene polymer having a cross-linked structure is a reaction product of an isobutylene polymer having an epoxy group and an isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group. The quantitative ratio of the isobutylene polymer having an epoxy group and the isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group in the reaction is 100:10 to 100:200 in terms of the molar ratio of the epoxy group to the carboxylic acid group and / or the carboxylic anhydride group.

15. An adhesive composition comprising: (A-1) an isobutylene polymer having an epoxy group, (A-2) an isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group, (B) a plasticizer that is liquid at 25°C and has a viscosity of less than 10,000 mPa·s at 25°C, and (C) a liquid polyolefin and / or liquid rubber which is liquid at 25°C and has a viscosity of 10000 mPa·s or more at 25°C, The quantitative ratio of the isobutylene polymer having an epoxy group and the isobutylene polymer having a carboxylic acid group and / or a carboxylic anhydride group in the reaction is 100:10 to 100:200 in terms of the molar ratio of the epoxy group to the carboxylic acid group and / or the carboxylic anhydride group.

16. A method for manufacturing an adhesive sheet, comprising the following steps: The adhesive composition according to claim 15 in a varnish form is applied onto a support and dried by heating to form an adhesive composition layer, wherein a cross-linked structure is formed in the adhesive composition layer.

17. A method for manufacturing an adhesive sheet, comprising the following steps: The adhesive composition according to claim 15 in a varnish form is applied onto a support and heated and dried to form an adhesive composition layer, in which a cross-linked structure is formed by the reaction of the epoxy group of the isobutylene polymer (A-1) having an epoxy group with the carboxylic acid group and / or carboxylic acid anhydride group of the isobutylene polymer (A-2) having a carboxylic acid group and / or a carboxylic acid anhydride group.

Citation Information

Patent Citations

  • Sealing sheet, and method for producing and evaluating the same

    JP2016186843A

  • Assembly layers for flexible displays

    JP2018526469A

  • Comforter

    JP2019180696A

  • Rubber composition and tacky tape having high strength

    JP1998036597A

  • Composition, adhesive, and adhesive sheet

    WO2019012905A1